1992
DOI: 10.1111/j.1365-2249.1992.tb03019.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of efferent limb of testicular autoimmune response by a regulatory CD4+ T cell line in mice

Abstract: SUMMARYA murine Tcell line (designated as CTs) as a mediator of suppression of exfjerimental autoimmune orchitis (EAO) was established. The method of establishment oIC.Ts cell line was preparing spleen eeils from C3H/He mice hyperimtnunized with testicular germ eelts (TC) and the repeated selection of the lymphocytes in vitro by stimulation with mouse testicular antigens (mTA). The CTs cells were Thy 1.2 • .surface immunoglobulin .CD3' .CD4' andCD8 . Thecellscould suppress the induction of EAO when transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…[951][952][953] Studies on pancreatic islet cell allografts in the mouse testis indicate that activated or memory T cells directed against graft antigens are destroyed when they enter the testis environment and that graft antigen-specific Treg cells are preferentially produced. 954,955 Isolation of a CD4 + T cell line that was able to downregulate the development of adoptive transfer of autoimmune orchitis in mice has been reported, 956 and a crucial role for Treg cells in controlling the development of orchitis in response to vasectomy also has been demonstrated in mice. 957 A substantial increase in evidence linking Treg cells and other regulatory T cell subsets to the control of testicular immune responses can be anticipated in the near future.…”
Section: Immune Tolerance and Immunoregulationmentioning
confidence: 99%
“…[951][952][953] Studies on pancreatic islet cell allografts in the mouse testis indicate that activated or memory T cells directed against graft antigens are destroyed when they enter the testis environment and that graft antigen-specific Treg cells are preferentially produced. 954,955 Isolation of a CD4 + T cell line that was able to downregulate the development of adoptive transfer of autoimmune orchitis in mice has been reported, 956 and a crucial role for Treg cells in controlling the development of orchitis in response to vasectomy also has been demonstrated in mice. 957 A substantial increase in evidence linking Treg cells and other regulatory T cell subsets to the control of testicular immune responses can be anticipated in the near future.…”
Section: Immune Tolerance and Immunoregulationmentioning
confidence: 99%
“…Most recently, we developed another model for the suppression of this type of EAO by a CD4+ suppressively regulatory cell line (designated CTs) [12]. The CTs line was derived from C3H/He mice that were injected with TC subcutaneously 10 times at 2-week intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Suppressive effects mediated by antigen-specific T cells have been documented in mice in several autoimmune disease models [8][9][10][11][12][27][28][29]. It is therefore of interest to characterize further suppressor cells that may be involved in the control of autoimmune phenomena in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously established that two subcutaneous injections of viable syngeneic testicular germ cells (TGC) can induce CD4+ T‐cell‐dependent EAO in both A/J and C3H/He mice at a very high incidence (Itoh et al ., ). Also, adoptive transfer experiments revealed that CD4+ T lymphocytes, but not B cells or immune serum, are crucial for the TGC‐induced EAO (Itoh et al ., , , ). These studies demonstrated that cellular rather than humoral immunity against TGC antigens is critical for EAO induction (Itoh et al ., ; Naito & Itoh, ; Tokunaga et al ., ).…”
Section: Introductionmentioning
confidence: 99%